Efficacy and safety of direct-acting antivirals in treatment of hepatitis C patients in Republic of Srpska: A real-life study - verhaz, antonija a (Scripta Medica, 2019)
The purpose of this study was to assess the antiviral efficacy and safety of the direct-acting antivirals (DAAs) in therapy of chronic hepatitis C virus (HCV) infection. This real-life multi-centric study was performed in Clinic for infectious diseases University clinical centre Republic of Srpska Banja Luka and it included a total of 89 patients. All patients received the adequate doses of ombitasvir (OBV)/paritaprevir (PTV)/ritonavir (RTV) + dasabuvir (DSV) plus ribavinin (RBV). RBV was given to all patients except to those with HCV sub-genotype 1b. DSV was not administered to patients infected with HCV genotype 4. For the majority of patient the treatment duration was 12 weeks. Ten patients with liver cirrhosis the duration of treatment was 24 weeks. Viraemia was assessed at four points in time: at baseline, four weeks after the beginning of treatment (rapid viral response, RVR), 12 or 24 weeks after the beginning of treatment (end of treatment response - ETR), and 12 weeks after the end of treatment (sustained viral response - SVR). Complete ETR after 12 weeks of treatment was achieved in 79 patients, while in 10 high-risk patients it was achieved after 24 weeks of treatment. Full SVR was recorded in 88 patients 12 weeks after the end of treatment. This therapy was well tolerated and mild adverse effects were recorded in only 10 patients. Treatment of patients with chronic HCV infection with OBV/PTV/RTV + DSV + RBV resulted in excellent antiviral activity and mild adverse events. Key words: Hepatitis C virus; Ombitasvir; Paritaprevir; Ritonavir; Dasabuvir; Ribavirin